Who is the human being?: an ecumenical approach to theological anthropology - Noble, Ivana; Širka, Zdenko Š.; Noble, Tim (Studies in theology and religion, 2026)
"Is being human a given, or is it something one grows into throughout one's life? Is possible to be and to become human without freedom, other people, nature, God? Offering interdisciplinary insights into such questions, this volume draws on the Bible and the classics of Christian in main language traditions, as well as contemporary debates on individualism, social responsibility, gender, and ecology. It explores narratives about human identity, how being and becoming human features in rituals and symbols, and theological models used by Christian anthropology over the centuries It looks at the human in the landscape, culture, and society, at the church, and considers the nature of discernment, formulating and reformulating moral values, and wrestling with new challenges. Contributors are: Pavol Bargár, Kateřina Kočandrle Bauer, Viorel Coman, Denisa Červenková, Ondřej Fischer, Pavel Hošek, Petr Jandejsek, Ondřej Kolář, Tabita Landová, Ivana Noble, Tim Noble, Libor Ovečka, Aristotle Papanikolaou, Mireia Ryšková, Zdenko Širka, František Štěch, Martin Vaňáč, and Michaela Vlčková. First published in Czech as Kdo je člověk? Teologická antropologie ekumenicky by Karolinum, Prague, 2021"-- Provided by publisher